From "waste to gold": a one-pot method to synthesize ultrafinely dispersed Fe2O3-based nanoparticles on N-doped carbon for synergistic and efficient water splitting1. Issue 22 (14th June 2015) - Su, Diefeng; wang, Jing; Jin, Haiyan; Gong, Yutong; Li, Mingming; Pang, Zhenfeng; Wang, Yong
<x xml:space="preserve">Abstract</x> We report a novel, simple, and one-pot method for the synthesis of ultrafinely dispersed iron oxide based nanoparticles (NPs) embedded in a nitrogen doped carbon matrix (denoted as Fe2O3/Fe@CN).